2017
DOI: 10.1080/10942912.2017.1381704
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of wax oleogels rich in high oleic acid

Abstract: Dual and triple combinations of high oleic acid sunflower oil (SO), SO, and blend oil (BO) were used to produce carnauba wax (CW) oleogels (OGs). Fatty acid composition, solid fat content (SFC), and rheological and textural properties of these OGs were determined and compared to laboratorymanufactured margarine. Fatty acid composition, SFC, rheological properties, and firmness value of the OGs were significantly influenced by oil combinations. The storage modulus (G') value was higher than the loss modulus (G'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Using different blends of oils including HO sunflower and HO rapeseed showed that wax oleogels have some similar properties (textural, rheological, and solid fat content) to those of commercial shortenings and margarines obtained with palm oil. The development of HO oilseed‐based soft matter could be used in food formulas reducing saturated fatty acid the diet (Onacik‐Gür and Żbikowska, 2020; Pehlivanoglu et al, 2017).…”
Section: Replacing Trans Fatty Acids (Tfa) In Food Processingmentioning
confidence: 99%
“…Using different blends of oils including HO sunflower and HO rapeseed showed that wax oleogels have some similar properties (textural, rheological, and solid fat content) to those of commercial shortenings and margarines obtained with palm oil. The development of HO oilseed‐based soft matter could be used in food formulas reducing saturated fatty acid the diet (Onacik‐Gür and Żbikowska, 2020; Pehlivanoglu et al, 2017).…”
Section: Replacing Trans Fatty Acids (Tfa) In Food Processingmentioning
confidence: 99%
“…Waxes containing a long chain of alkanes and esters are much more efficient in vegetable oil gel than waxes made of short-chain alkanes [ 21 ]. Many natural waxes such as carnauba wax, candelilla wax, and beeswax, etc., have been reported as an efficient oleogelator because of their ability to crystallize the vegetable oil at lower concentrations [ 22 ]. The lower wax concentration for formulating oleogels is attributed to the presence of long-chain esters in the SFW.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, increasing oleogelator concentration caused to increasing G* (Patel et al, 2013). Also, increasing G* was related to increasing the gel strength (Patel et al, 2013;Pehlivanoglu et al, 2018). In that regard, it could be said that gel strength of oleogel was increased w.r.t.…”
Section: Rheological Properties Of Oleogelsmentioning
confidence: 95%